2021
DOI: 10.1038/s41598-021-96569-0
|View full text |Cite
|
Sign up to set email alerts
|

The integration of training and off-training activities substantially alters training volume and load analysis in elite rowers

Abstract: Training studies in elite athletes traditionally focus on the relationship between scheduled training (TRAIN) and performance. Here, we added activities outside of scheduled training i.e., off-training (OFF) contributing to total training (TOTAL) to evaluate the contribution of OFF on performance. Eight elite rowers recorded OFF and TRAIN during waking hours for one season (30–45 weeks) with multisensory smartwatches. Changes in performance were assessed via rowing ergometer testing and maximum oxygen uptake (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…For example, in particular during the Ardennes Classics, the cyclists might perform some domestic duties when they are at home on training days in‐between 1‐day classic races. In line with this, research among elite rowers 31 and academy football players 32 also shows considerable off‐training activities for some individuals. However, no definitive conclusion regarding the cause of the higher PAL‐value can be made as non‐exercise activities were not directly registered.…”
Section: Discussionmentioning
confidence: 62%
“…For example, in particular during the Ardennes Classics, the cyclists might perform some domestic duties when they are at home on training days in‐between 1‐day classic races. In line with this, research among elite rowers 31 and academy football players 32 also shows considerable off‐training activities for some individuals. However, no definitive conclusion regarding the cause of the higher PAL‐value can be made as non‐exercise activities were not directly registered.…”
Section: Discussionmentioning
confidence: 62%
“…The rowers were instructed to maintain an average power output as close as possible for each stage [ 1 ]. The test was automatically ended if a rower failed to increase the mechanical power output within a 7 W range of five strokes [ 44 ]. Peak power output (PPO) was defined as the highest stage the subject successfully completed.…”
Section: Methodsmentioning
confidence: 99%
“…Given the abundance of data and metrics available to coaches and athletes, there is increased interest in physiological forecasting, or predicting outcomes or performances based on an array of variables that may be collected using wearable technology and other means. These technologies may be able to quantify stress and recovery outside of the training period to improve quantification of training load [137]. It seems clear that HRV alone is not linearly predictive of performance, as it has been observed that HRV may diminish slightly during the peaking phase [13].…”
Section: Future Directionsmentioning
confidence: 99%